2018
DOI: 10.1103/physrevlett.120.263602
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Based Optical Mirror Coatings for Ultrahigh Precision Metrology and Sensing

Abstract: Thermal noise of highly reflective mirror coatings is a major limit to the sensitivity of many precision laser experiments with strict requirements such as low optical absorption. Here, we investigate amorphous silicon and silicon nitride as an alternative to the currently used combination of coating materials, silica, and tantala. We demonstrate an improvement by a factor of ≈55 with respect to the lowest so far reported optical absorption of amorphous silicon at near-infrared wavelengths. This reduction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Therefore, in the absence of data for this coating at cryogenic temperatures, we have used the room-temperature value as a likely upper limit on the cryogenic loss. For the material presented in [29], the optimum heat-treatment temperature to minimize the optical absorption was 450 • C. There is evidence of a decrease of the mechanical loss of a-Si for slightly higher heat-treatment temperatures than 400 • C [30,49]. Therefore, an upper limit of 0.17 × 10 −4 for the loss is still valid.…”
Section: -7mentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, in the absence of data for this coating at cryogenic temperatures, we have used the room-temperature value as a likely upper limit on the cryogenic loss. For the material presented in [29], the optimum heat-treatment temperature to minimize the optical absorption was 450 • C. There is evidence of a decrease of the mechanical loss of a-Si for slightly higher heat-treatment temperatures than 400 • C [30,49]. Therefore, an upper limit of 0.17 × 10 −4 for the loss is still valid.…”
Section: -7mentioning
confidence: 95%
“…The requirement that the optical absorption is <5 ppm makes development of suitable materials even more challenging. Materials with low mechanical loss such as a-Si [29,30] and silicon nitride (SiN) [30,31] are promising, but show too high optical absorption. Different options for doping low-absorbing Ta 2 O 5 are also under investigation [32,33], but so far could not match the thermal-noise requirements.…”
Section: Coating Thermal Noise In the Einstein Telescopementioning
confidence: 99%
“…Recent results [35][36][37] have shown that coatings of amorphous silicon (aSi) deposited through various techniques (e-beam evaporation, reactive low-voltage ion plating, IBS) can feature very high refractive index (n ∼ 3.6) and very low internal friction (10 −5 < φ c < 10 −4 ); however, their optical absorption (10 −5 < k < 10 −4 , for 1064 < λ < 2000 nm and 20 < T < 290 K) is still larger than the requirements of GW interferometers. [31] and latest coating samples annealed in air at 900 • C for 10 hours, compared to current values of Ta 2 O 5 -TiO 2 coatings annealed in air at 500 • C for 10 hours (from Fig.…”
Section: Amorphous Siliconmentioning
confidence: 99%
“…For a semiconductor material such as silicon nitride and amorphous silicon, however, the optical absorption at cryogenic temperature is expected to be lower than that at room temperature owing to the reduced interband transition at low temperature. Experimental evidence showed that the absorption coefficient of an amorphous silicon film, which is also a potential high-refractive-index material for the mirror coatings of the next-generation laser interferometer gravitational wave detector, at cryogenic temperature was ≈ 3 times lower than that at room temperature [36]. The thermalrefractive effect, dn/dT, is positive for most of the optical materials.…”
Section: A Structures For the Qw Multilayer High Reflectorsmentioning
confidence: 99%